Antimycotic Activity of Lactic Acid Bacteria on the Growth of Cheese Contaminating Molds - Fatim Illianingtyas; B S.L Jenie; L Nuraida (Jurnal Teknologi dan Industri Pangan, 2006)
Local cheese is frequently contaminated by toxigenic molds which is harmful for human health. Lactic acid bacteria have been proven to inhibit the growth of toxigenic mold in some food products. The research was aimed to study the activity of indigenous lactic acid bacteria to inhibit the growth of toxigenic molds in local cheese. The molds studied were isolated from local cheese production (Gouda type). The cheese contaminating molds were identified as Penicillium sp. and Aspergillus sp. Nine species of indigenous lactic acid bacteria (LAB) were tested for antimycotic activities, i.e. Lactobacillus plantarum kik, Lactobacillus plantarum sa, Lactobacillus plantarum pi28a, Lactobacillus plantarum dd, Lactobacillus coryneformis, Lactobacillus brevis, Lactococcus piscium, Leuconostoc mesenteroides, and Leuconostoc paramesenteroides. The research revealed that the promising indigenous LAB which inhibited the contaminating molds was Lb plantarum pi28a. Application of Lb plantarum pi28a on local cheese production could inhibit the growth of Penicillium sp. and Aspergillus sp. up to 12 days. Key words: cheese, contaminating mold, lactic acid bacteria